Let's talk numbers: a qualitative study of community-dwelling US adults to understand the role of numeracy in the management of heart failure. Issue 9 (19th September 2018) - Sterling, Madeline R; Silva, Ariel F; Robbins, Laura; Dargar, Savira K; Schapira, Marilyn M; Safford, Monika M
Abstract : Objective: To examine the perspectives of adults with heart failure (HF) about numerical concepts integral to HF self-care. Setting: This qualitative study took place at an urban academic primary care practice. Participants: Thirty men and women aged 47–89 years with a history of HF were recruited to participate. Eligibility criteria included: a history of HF (≥1 year), seen at the clinic within the last year, and a HF hospitalisation within the last 6 months. Non-English speakers and those with severe cognitive impairment were excluded. Methods: In-depth semistructured interviews were conducted. Participants were interviewed about numeracy across three domains of HF self-care: (1) monitoring weight, (2) maintaining a diet low in salt and (3) monitoring blood pressure. Interviews were audio-taped, transcribed verbatim and analysed using grounded theory and word cloud techniques. Results: Five key themes reflecting participants' attitudes towards numerical concepts pertaining to weight, diet and blood pressure were identified: (1) Communication between healthcare providers and patients is a complex, multistage process; (2) Patients possess a wide range of knowledge and understanding; (3) Social and caregiver support is critical for the application of numerical concepts; (4) Prior health experiences shape outlook towards numerical concepts and instructions and (5) Fear serves as a barrier and a facilitator to carrying out HF self-care tasks that involve numbers. The findings informed a theoretical framework of health numeracy in HF. Conclusion: Effective communication of numerical concepts which pertain to HF self-care is highly variable. Many patients with HF lack basic understanding and numeracy skills required for adequate self-care. As such, patients rely on caregivers who may lack HF training. HF-specific training of caregivers and research that seeks to elucidate the intricacies of the patient–caregiver relationship in the context of health numeracy and HF self-care are warranted.